On Hardy-Hilbert-type inequalities with α-fractional derivatives - Marwa M. Ahmed; Wael S. Hassanein; Marwa Sh. Elsayed; Dumitru Baleanu; Ahmed A. El-Deeb (AIMS Mathematics, 2023)
In the current manuscript, new alpha delta dynamic Hardy-Hilbert inequalities on time scales are discussed. These inequalities combine and expand a number of continuous inequalities and their corresponding discrete analogues in the literature. We shall illustrate our results using Hölder's inequality on time scales and a few algebraic inequalities.